The Use of Show and Tell Strategy in Teaching Vocabulary of The 7th Grade Students at SMPN 3 Pujut - Fitriana, Sulis Mai; Nawawi, Nawawi; Putera, Lalu Jaswadi; Melani, Boniesta Zulandha (Jurnal Ilmiah Profesi Pendidikan, 2025)
This research investigates the effectiveness of the Show and Tell (SAT) strategy in teaching vocabulary to the seventh-grade students of SMPN 3 Pujut. Vocabulary is one of the essential components in English learning, and many students still face difficulties in mastering it. Therefore, an appropriate strategy is needed to improve their vocabulary achievement. The purpose of this study was to determine whether there was a significant difference in students’ vocabulary mastery between those taught using the Show and Tell strategy and those taught through conventional methods, as well as to find out whether the Show and Tell strategy was effective for teaching vocabulary. This study employed a quasi-experimental research design with a quantitative approach, using pre-test and post-test instruments. The sample consisted of 56 students divided into two groups: 28 students in the experimental class and 28 students in the control class. Data were collected through vocabulary tests and analyzed using SPSS version 25, including tests of normality, homogeneity, and an independent samples t-test. The results revealed that the experimental groups mean score increased from 61.07 in the pre-test to 89.10 in the post-test, while the control group’s mean rose from 63.92 to 84.28. The t-test value (t0 = 2.024; p = 0.048 < 0.05) indicated a significant difference between the two groups. These findings confirmed that the Show and Tell strategy was more effective in improving students’ vocabulary mastery compared to the conventional strategy. In conclusion, the Show and Tell strategy significantly enhanced students’ vocabulary mastery and made the learning process more interactive, contextual, and engaging. Therefore, it is recommended that English teachers implement this strategy in their classrooms to promote active participation, motivation, and better vocabulary retention among students.